On testimonial justice online. Nuancing Karen Frost-Arnold's optimistic virtue epistemology - Velasco Arias, Gonzalo (Daimon Revista Internacional de Filosofia, 2024)
En What Should We Be Online, Karen Frost-Arnold defiende una cierta aproximación a las virtudes epistémicas que resista al pesimismo acerca de la posibilidad de que nuestra agencia epistémica online sea responsable y justa. Sobre la base de una epistemología veritista, su propuesta supera tanto el individualismo responsabilista como la crítíca socio-estructural que delega toda responsabilidad en transformaciones institucionales. La autora identifica en el online lurking una actividad exclusiva de la agencia epistémica online capaz de proporcionar una exposición a mensajes de personas discriminadas por injusticias epistémicas. Para Frost-Arnold, a su vez, esto implica la posibilidad de que el lurker experimente fricciones epistémicas que favorecerán una disposición más fiable a ser justos a la hora de dar crédito a los testimonios de personas discriminadas. En esta nota matizaré esta postura optimista, alegando el individualismo epistémico que subyace. Apuntaré a un modelo de virtudes grupales como posible solución. In Who Should We Be Online, Karen Frost-Arnold advocates an approach to epistemic virtues that resists pessimism about the possibility of our online epistemic agency being responsible and socially just. On the basis of a veritist epistemology, her proposal overcomes both responsibilist individualism and the socio-structural critique that delegates all responsibility to institutional transformations. The author identifies in online lurking an activity unique to online epistemic agency that can provide exposure to messages from people discriminated against by epistemic injustices. For Frost-Arnold, moreover, this implies the possibility of the lurker experiencing epistemic frictions that will favour a more reliable willingness to be fair in giving credit to the testimonies of those discriminated against. In this note I will qualify this optimistic stance, arguing the epistemic individualism that underlies it. I will point to a group virtue model as a possible solution.